2021
DOI: 10.1111/nyas.14599
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction and potential mitochondrial protectant treatments in tendinopathy

Abstract: Tendinopathy is a common musculoskeletal condition that affects a wide range of patients, including athletes, laborers, and older patients. Tendinopathy is often characterized by pain, swelling, and impaired performance and function. The etiology of tendinopathy is multifactorial, including both intrinsic and extrinsic mechanisms. Various treatment strategies have been described, but outcomes are often variable, as tendons have poor intrinsic healing potential compared with other tissues. Therefore, several no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 123 publications
(223 reference statements)
0
12
0
Order By: Relevance
“…[ 30 ] Normal cell proliferation is promoted by hyperactive mitochondria under material‐ and energy‐sufficient conditions. [ 31 ] As assayed by the mitochondrial fluorescence probe, the mitochondrial density in the Him‐MFM group were the highest. Correspondingly, the ATP/ADP level was 1.55 ± 0.07 in the Him‐MFM group, which was also higher than those of 1.07 ± 0.02, 1.13 ± 0.04, 1.02 ± 0.05, and 0.99 ± 0.06 in the other groups.…”
Section: Resultsmentioning
confidence: 99%
“…[ 30 ] Normal cell proliferation is promoted by hyperactive mitochondria under material‐ and energy‐sufficient conditions. [ 31 ] As assayed by the mitochondrial fluorescence probe, the mitochondrial density in the Him‐MFM group were the highest. Correspondingly, the ATP/ADP level was 1.55 ± 0.07 in the Him‐MFM group, which was also higher than those of 1.07 ± 0.02, 1.13 ± 0.04, 1.02 ± 0.05, and 0.99 ± 0.06 in the other groups.…”
Section: Resultsmentioning
confidence: 99%
“…The transition from limited ATP synthesis to ROS production leads to oxidative damage to mitochondria and other organelles, which could convert TDSCs to a pro‐inflammatory state, thereby initiating the senescence program. [ 43 , 44 ] Moreover, severe oxidative stress could lead to apoptosis of tenocytes, which is mediated by mitochondrial release of cytochrome C and triggering caspase‐3 activation. [ 45 ] As the main pro‐inflammatory cytokines in SASP, the expression of IL‐1 β , IL‐6, TNF‐ α , and IFN‐ γ was down‐regulated in H 2 O 2 + CeNPs group, demonstrating a remission of the inflammatory state of the TDSCs (Figure 6B–E ).…”
Section: Resultsmentioning
confidence: 99%
“…Pathologically, oxidative stress mediates inflammatory activation, including activation of M1 macrophages and unrestricted secretion of pro‐inflammatory factors. [ 43 , 54 ] Meanwhile, M1 macrophage polarization and persistent inflammation initiate senescence programs. [ 44 , 55 ] And SASPs, including IL‐1 α , IL‐6, and IFN‐ γ could induce M1 polarization of macrophages, thereby enhancing the early inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
“…T he pathogenesis of tendinopathy is multifactorial and complex, and current treatment strategies are associated with variable efficacy and a high rate of recurrent symptoms, possibly owing to the poor regenerative potential of tendon and incomplete characterization of the underlying pathophysiology 1,33 . Our recent studies have revealed the role of mitochondrial dysfunction in the onset and progression of tendinopathy 3,6 . Thus, agents that target mitochondria may represent an effective strategy for treatment of tendinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are the powerhouses of cells and play fundamental roles in basic development and repair processes 3,4 . Mitochondrial dysfunction has been found to influence tendon healing following rotator cuff injury 5 .…”
mentioning
confidence: 99%